2017
DOI: 10.1161/jaha.117.005892
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease and Risk of Ischemic Heart Disease: An Updated Meta‐Analysis of Cohort Studies

Abstract: BackgroundSeveral immune‐mediated diseases have been shown to be associated with an increased risk of cardiovascular disease. However, studies evaluating the association between inflammatory bowel disease and risk of cardiovascular disease reported inconsistent results. We assessed the association between inflammatory bowel disease and risk of ischemic heart disease in a meta‐analysis of cohort studies.Methods and ResultsWe conducted a literature search of PubMed and Embase up to October 2016 to identify relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
84
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 55 publications
7
84
1
6
Order By: Relevance
“…Two meta‐analyses concluded that cardio/cerebrovascular risk is increased in IBD, particularly among women, which is in accordance with our present results. The larger effect noted in female IBD patients might be related to the fact that the role of inflammation in coronary heart disease seems to be greater in women than in men.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Two meta‐analyses concluded that cardio/cerebrovascular risk is increased in IBD, particularly among women, which is in accordance with our present results. The larger effect noted in female IBD patients might be related to the fact that the role of inflammation in coronary heart disease seems to be greater in women than in men.…”
Section: Discussionsupporting
confidence: 93%
“…In terms of age and risk, more prominent association of IBD with increased CVD risk in younger patients (vs older patients) has been consistently reported . Consistently, we found that, among CD patients, the magnitude of the increase in cardiovascular risk is higher in younger individuals (<40 vs ≥40 years, especially <30 years old), which may be related to inflammation levels.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The risk was higher in younger women less than 50 years old. In sub-analyses, controlling for obesity or smoking did not influence the outcome [125]. In a smaller retrospective controlled cohort study spanning 30 years from Olmsted county, USA, the risk for both acute myocardial infarct (CD and UC) and heart failure (UC) was found to be increased.…”
Section: Comorbidities In Obesity Shared With Inflammatory Bowel Diseasementioning
confidence: 86%
“…Assim como outras doenças crônicas imunomediadas, a DC também está associada a uma maior incidência de eventos CV (DAC, AVE, doença arterial periférica e isquemia mesentérica), independentemente da presença dos fatores de risco clássicos para aterosclerose [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] . Diversas coortes retrospectivas realizadas por meio de grandes bases de dados populacionais, com envolvimento de até cerca de 150.000 pacientes com DC, evidenciam risco de doença isquêmica do miocárdio aumentado em até 31% em relação à população geral 20,22,26,27,34 .…”
Section: A Doença De Crohn E a Ateroscleroseunclassified